Covalently Functionalized MXenes for Highly Sensitive Humidity Sensors - Janica, Iwona; Montes-Garcia, Veronica; Urban, Francesca; Hashemi, Payam; Nia, Ali Shaygan; Feng, Xinliang; Samori, Paolo; Ciesielski, Artur (Small Methods, 2023)
Transition metal carbides and nitrides (MXenes) are an emerging class of 2D materials, which are attracting ever-growing attention due to their remarkable physicochemical properties. The presence of various surface functional groups on MXenes’ surface, e.g., -F, -O, -OH, -Cl, opens the possibility to tune their properties through chemical functionalization approaches. However, only a few methods have been explored for the covalent functionalization of MXenes and include diazonium salt grafting and silylation reactions. Here, an unprecedented two-step functionalization of Ti3C2Tx MXenes is reported, where (3-aminopropyl)triethoxysilane is covalently tethered to Ti3C2Tx and serves as an anchoring unit for subsequent attachment of various organic bromides via the formation of C-N bonds. Thin films of Ti3C2Tx functionalized with linear chains possessing increased hydrophilicity are employed for the fabrication of chemiresistive humidity sensors. The devices exhibit a broad operation range (0–100% relative humidity), high sensitivity (0.777 or 3.035), a fast response/recovery time (0.24/0.40 s ΔH−1, respectively), and high selectivity to water in the presence of saturated vapors of organic compounds. Importantly, our Ti3C2Tx-based sensors display the largest operating range and a sensitivity beyond the state of the art of MXenes-based humidity sensors. Such outstanding performance makes the sensors suitable for real-time monitoring applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: covalent functionalization; humidity sensors; MXenes; Ti; water receptors